Sports Nutrition Knowledge among Mid-Major Division I University Student-Athletes - Ashley Andrews; Janet R. Wojcik; Joni M. Boyd; Charles J. Bowers (Journal of Nutrition and Metabolism)
Competitive athletes have goals to optimize performance and to maintain healthy body composition. Sports nutrition is a component of training programs often overlooked by student-athletes and their coaches. The purpose of this study was to examine student-athletes’ sports nutrition knowledge across sex, class level, team, and completion of prior nutrition coursework. Participants included 123 mid-major Division I university student-athletes (47 females and 76 males) from baseball, softball, men’s soccer, track and field, and tennis. The student-athletes completed a survey questionnaire to determine adequate sports nutrition knowledge (mean ≥ 75%). The overall mean sports nutrition knowledge score for the student-athletes was 56.9% which was considered inadequate sports nutrition knowledge (mean < 75%). Only 12 student-athletes achieved adequate sports nutrition knowledge score of 75% or higher. There were no differences by sex, class level, team, and completion of prior nutrition coursework. Student-athletes’ inadequate sports nutrition knowledge may place them at nutrition risk, lead to impaired performance, and affect their lean body mass and energy levels. Athletics personnel should not assume student-athletes have adequate sports nutrition knowledge. Athletic departments may make available a board certified Sports Dietitian or Registered Dietitian and offer classroom or online courses facilitating student-athletes to optimize nutrition knowledge and behaviors.